Validation of MCMC-Based Travel Simulation Framework Using Mobile Phone Data - Gong, Suxia; Saadi, Ismaïl; Teller, Jacques; Cools, Mario (Frontiers in Future Transportation, 2021)
An essential step in agent-based travel demand models is the characterization of the population, including transport-related attributes. This paper looks deep into various mobility data in the Province of Liège, Belgium. Based on the data stemming from the 2010 Belgian HTS, i.e., BELDAM, a Markov Chain Monte Carlo (MCMC) sampling method combined with a cross-validation process is used to generate socio-demographic attributes and trip-based variables. Besides, representative micro-samples are calibrated using data about the population structure. As a critical part of travel demand modeling for practical applications in the real-world context, validation using various data sources can contribute to the modeling framework in different ways. The innovation in this paper lies in the comparison of outputs of MCMC with mobile phone data. The difference between modeled and observed trip length distributions is studied to validate the simulation framework. The proposed framework infers trips with multiple attributes while preserving the traveler’s socio-demographics. We show that the framework effectively captures the behavioral complexity of travel choices. Moreover, we demonstrate mobile phone data’s potential to contribute to the reliability of travel demand models.